On the necessity of gardening : an ABC of art, botany and cultivation - Barnas, Maria, 1973-; Cluitmans, Laurie, 1984-; Bruce, Jonny; Centraal museum (Utrecht, Pays-Bas). (Amsterdam : Valiz., 2021)
On the Necessity of Gardening tells the story of the garden as a rich source of inspiration. Over the centuries, artists, writers, poets and thinkers have each described, depicted and designed the garden in different ways. In medieval art, the garden was a reflection of paradise, a place of harmony and fertility, shielded from worldly problems. In the eighteenth century this image tilted: the garden became a symbol of worldly power and politics. The Anthropocene, the era in which man completely dominates nature with disastrous consequences, is forcing us to radically rethink the role we have given nature in recent decades. There is a renewed interest in the theme of the garden among contemporary makers. It is not a romantic desire that drives them, but rather a call for a new awareness of our relationship with the earth. Through many different essays and an extensive abecedarium, On the Necessity of Gardening reflects on the garden as a metaphor for society.00Exhibition: Centraal Museum, Utrecht, The Netherlands
On the Necessity of Gardening raconte l'histoire du jardin comme une riche source d'inspiration. Au fil des siècles, artistes, écrivains, poètes et penseurs ont chacun décrit, représenté et conçu le jardin de différentes manières. Dans l'art médiéval, le jardin était le reflet du paradis, un lieu d'harmonie et de fertilité, à l'abri des problèmes du monde. Au XVIIIe siècle, cette image a basculé : le jardin est devenu un symbole du pouvoir mondain et de la politique. L'Anthropocène, l'ère où l'homme domine complètement la nature avec des conséquences désastreuses, nous oblige à repenser radicalement le rôle que nous avons donné à la nature au cours des dernières décennies. Le thème du jardin connaît un regain d'intérêt chez les créateurs contemporains. Ce n'est pas un désir amoureux qui les anime, mais plutôt un appel à une nouvelle prise de conscience de notre rapport à la terre. À travers de nombreux essais différents et un vaste abécédaire, Sur la nécessité du jardinage réfléchit sur le jardin en tant que métaphore de la société.
boek
Keywords: Art des jardins -- Histoire; Art des jardins -- Thèmes, motifs; Botanique; Catalogues d'exposition.; Exhibition catalogs; Cultures; Abécédaires